Arthur et les Minimoys - Besson, Luc, 1959-; Freddie, Highmore; Mia Farrow; Ron Crawford; Penny Balfour; Doug Rand; Adam LeFevre; Jean Bejote Njamba; Saul Jephcott; Lee de Long; Christian Erickson; Eric Balliet; et al. (France Europa Corp., 2006)
Arthur is a spirited ten-year old whose parents are away looking for work, whose eccentric grandfather has been missing for several years, and who lives with his grandmother in a country house that, in two days, will be repossessed, torn down, and turned into a block of flats unless Arthur's grandfather returns to sign some papers and pay off the family debt. Arthur discovers that the key to success lies in his own descent into the land of the Minimoys, creatures no larger than a tooth, whom his grandfather helped relocate to their garden. Somewhere among them is hidden a pile of rubies, too. Can Arthur be of stout heart and save the day? Romance beckons as well, and a villain lurks.
Ten-year-old boy named Arthur has a lot on his plate: a real estate developer is about to snap up his grandma's home--and there's no way Arthur's going to hang around for his parents or grandparents to sort out the problem. Maybe the solution lies in his grandpa's secret treasure, which is hidden somewhere on the "other side" in the land of the Minimoys. The creatures that inhabit this world are just a tenth of an inch tall and live in perfect harmony with their environment. Arthur ventures into the world of the Minimoys, where he meets Princess Selenia and her brother Betameche. Together they set off to look for the treasure that will save his grandma.
Adventure awaits in your own backyard.
Language: English Subtitle: Turkish
Keywords: Animation; Adventure; Family; Fantasy